The Effect of the number of InGaN/GaN pairs on the photoelectrochemical properties of InGaN/GaN multi quantum wells - Bae, Hyojung; Park, Jun-Beom; Fujii, Katsushi; Lee, Hyo-Jong; Lee, Sang-Hyun; Ryu, Sang-Wan; Lee, June Key; Ha, Jun-Seok (ELSEVIER SCIENCE BV, 2017)
In this study, the effects of the number of quantum well (QW) pairs on the photoelectrochemical (PEC) properties of InGaN/GaN multi-QW structures (MQWs) were investigated. MQW samples were grown using metal-organic chemical vapor deposition, and their structural characteristics were confirmed by X-ray diffraction measurements. The photoluminescence measurements revealed that the optical properties of MQWs may be related to the PEC properties. The cyclic voltammetry data revealed that the saturated photocurrent density increased with increasing number of QW pairs; the photocurrent density of MQW5 was twice that of an nGaN reference. However, in the chronoamperometry measurement of the photoanode stability, MQWs with 3 QWs displayed the highest photocurrent stability, although the saturated photocurrent density was highest for MQW5. This was also confirmed by field-emission scanning electron microscopy of the surface morphology after PEC measurements. The stability and photocurrent density may be attributed to the quality of crystallinity of the MQWs. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: GENERATION; NANOWIRES